Analisis Pengaruh Arus Eksitasi pada Generator Sinkron Terhadap Pembebanan di PLTA Wlingi PT PJB Up Brantas - Istanto, Yudistira Heri (Jurnal Qua Teknika, 2019)
This study will discuss the effect of the Wlingi hydropower synchronous generator excitation current on each change of load to keep the nominal outtime voltage of the generator with the changing voltage of 150 kV. Data analysis was obtained from the Wlingi Hydroelectric Daily Operation Report (LHO) in accordance with the changes in generator load or changes in transmission voltage values ​​to determine the effect on changes in AVR excitation currents. The next daily data obtained is compared with the initial setting or characteristics of the AVR when the Commissioning Test, the resulting deviation will be used as input for Engineering UP Brantas in carrying out the next corrective action. Thus the reliability of the Wlingi PLTA in serving P2B to maintain the stability of the Java-Bali 150 kV transmission system is maintained. So that it can contribute to improving company performance.